Analysis of the Holarctic Dictyoptera aurora Complex (Coleoptera, Lycidae) Reveals Hidden Diversity and Geographic Structure in Müllerian Mimicry Ring - Michal Motyka; Dominik Kusy; Renata Bilkova; Ladislav Bocak (Insects)
The elateroid family Lycidae is known for limited dispersal propensity and high species-level endemism. The red net-winged beetle, Dictyoptera aurora (Herbst, 1874), differs from all relatives by the range comprising almost the entire Holarctic region. Based on a five-marker phylogeny and 67 barcode entries (cox1-5′ mtDNA) from the whole range, we recovered two genetically distinct species within traditionally defined D. aurora and resurrected the name D. coccinata (Say, 1835) as the oldest available synonym for Nearctic populations. Yet, no reliable morphological trait distinguishes these species except for minute differences in the male genitalia. D. coccinata is a monophylum resulting from a single Miocene dispersal event, ~15.8 million years ago, and genetic divergence implies long-term isolation by the Bering Strait. Far East Asian and west European populations are also genetically distinct, although to a lower extent. Two independent colonization events established the Fennoscandian populations after the last glacial maximum. Besides intrinsic factors, the high morphological similarity might result from stabilizing selection for shared aposematic signals. The rapidly accumulating barcode data provide valuable information on the evolutionary history and the origins of regional faunas.